Minority Report - Francis Dominic Degnin PhD (SAGE Open, 2016)
The Epic of Gilgamesh attempts to answer the question of how, given the finality of death, one might find meaning and happiness in life. Many commentators argue that the text provides two separate, although ultimately unsatisfactory, alternatives. What these commentators appear to miss, however, is the possibility that these two solutions may not be separate. Using Levinas’s distinction between “need” and “desire,” I argue that, by the end of the Epic , they may in fact be synthesized into a single solution, one that suggests the priority of an affective moral grounding as prior to and more fundamental than intellectual solutions.